A note on the Banach lattice c_0( _2^n), its dual and its bidual - Lourenço, M.L.; Miranda, V.C.C. (Carpathian Mathematical Publications, 2023)
The main purpose of this paper is to study some geometric and topological properties of c_0-sum of the finite dimensional Banach lattice _2^n, its dual and its bidual. Among other results, we show that the Banach lattice c_0(_2^n) has the strong Gelfand-Philips property, but does not have the positive Grothendieck property. We also prove that the closed unit ball of l_∞(_2^n) is an almost limited set.